THU0272 Efficacy of oral prednisolone in active ankylosing spondylitis – results of a double blind placebo controlled trial. (23rd January 2014) - Haibel, H.; Fendler, C.; Listing, J.; Callhoff, J.; Braun, J.; Sieper, J.
Abstract : Background: To date no clinical trials are available showing efficacy of moderatly dosed prednisolone for the therapy of active ankylosing spondylitis (AS). Objectives: To evaluate the efficacy and safety of moderately dosed prednisolone versus placebo over 2 weeks in patients with active AS despite NSAID treatment. Methods: Of 39 patients enrolled, 36 finished the trial. Patients were randomized to one of 3 groups. Prednisolone was given double blind as 20 mg (n=13), 50 mg (n=12) or Placebo (PBO) (n=14) orally every day over 2 weeks. Mean age of the patients was 41 years (range 19-72), mean disease duration was 14 years (range 1-55), HLA-B27 was positive in 71% of patients. Clinical outcome assessments included disease activity (BASDAI), function (BASFI), metrology (BASMI), patient's global assessment and pain (PG), peripheral joint assessment, Berlin enthesitis score, and C-reactive protein (CRP). Primary endpoint of this study was improvement of BASDAI 50 at Week 2. Results: Mean change of BASDAI was significantly higher in the 50 mg group, p=0.026, when compared to PBO whereas this was not the case for the other groups: PBOversus 20 mg, p=n.s., 20 mg versus 50 mg, p=n.s. More patients reached a BASDAI 50 response in the 50 mg versus the PBO group when compared to the other groups, p=n.s. When looked for the 4 BASDAI 50 responders compared to the 8 non responders in the 50 mg group at screening they were significantly younger (35 vs 46 years), had a better spinal mobility (BASMI 2.5 vs. 4.8), higher CRP-values (59 mg/l vs 18 mg/l) lower BASDAI (5.8 vs. 6.6) and a lower BASFI levels (4.4 vs. 8.9). When looked for changes between screening and week 2 within the groups, in the 20 mg group significant improvements were found for BASDAI and pain and in the 50 mg group for BASDAI, BASDAI morning stiffness, BASFI, PG, pain and BASMI (table). Other results are listed in the table below. Conclusions: Prednisolone 50 mg showed significantly higher response rates when compared to placebo or 20 mg prednisolone for different outcome parameters in patients with active ankylosing spondyitis. However, 20 mg of prednisolone per day did not show such an effect and the 50 mg high dosis of prednisolone does not seem to be acceptable for a longer treatment period. Disclosure of Interest: H. Haibel Grant/Research support from: Merck Germany KgaA, Consultant for: Abbott GmbH, Speakers Bureau: Pfizer, Wyeth Pharmaceuticals, Merck Sharp and Dohme/Schering Plough, Abbott GmbH, C. Fendler: None Declared, J. Listing: None Declared, J. Callhoff: None Declared, J. Braun Grant/Research support from: Pfizer, Wyeth Pharmaceuticals, Merck Sharp and Dohme/Schering Plough, Abbott GmbH, Consultant for: Pfizer, Wyeth Pharmaceuticals, Merck Sharp and Dohme/Schering Plough, Abbott GmbH, UCB, Speakers Bureau: Pfizer, Wyeth Pharmaceuticals, Merck Sharp and Dohme/Schering Plough, Abbott GmbH, UCB, J. Sieper Grant/Research support from: Pfizer, Wyeth Pharmaceuticals, Merck Sharp and Dohme/Schering Plough, Abbott GmbH, Merck Germany KgaA, Consultant for: Pfizer, Wyeth Pharmaceuticals, Merck Sharp and Dohme/Schering Plough, Abbott GmbH, UCB, Speakers Bureau: Pfizer, Wyeth Pharmaceuticals, Merck Sharp and Dohme/Schering Plough, Abbott GmbH, UCB